Islamic finance in western higher education developments and prospects - Belouafi, Ahmed; Belabes, Abderrazak; Trullols, Cristina (Palgrave Macmillan, 2012)
This is the first of its kind in its topical coverage of the developments and prospects of Islamic finance education at Western higher education. Intended to establish itself as a unique reference for academics and researchers this book gives an insight into ethics and values in curricula development at business schools and in finance departments.